Ceftazidime as initial therapy for suspected bacterial infections in hospitalized pediatric patients. - Reed, M D (1984)
Ceftazidime, a new beta-lactam antibiotic, was used to treat 60 children with suspected bacterial infections occurring outside the central nervous system. The patients ranged in age from 0.1 to 21 years and received 30 mg of ceftazidime per kg up to a total single dose of 1 g administered every 8 h. Fifty-three pathogens were isolated from 43 children before the initiation of therapy. All children responded clinically, although one child failed bacteriologically and five children were considered colonized at the end of ceftazidime therapy. Adverse reactions associated with ceftazidime administration were primarily alterations in laboratory parameters and were clinically insignificant. Ceftazidime administered on an 8-h dosing regimen is effective monotherapy for the treatment of childhood infections.